Performance and usability of pre‐operative prediction models for 30‐day peri‐operative mortality risk: a systematic review. (23rd February 2023) - Vernooij, J. E. M.; Koning, N. J.; Geurts, J. W.; Holewijn, S.; Preckel, B.; Kalkman, C. J.; Vernooij, L. M.
Summary: Estimating pre‐operative mortality risk may inform clinical decision‐making for peri‐operative care. However, pre‐operative mortality risk prediction models are rarely implemented in routine clinical practice. High predictive accuracy and clinical usability are essential for acceptance and clinical implementation. In this systematic review, we identified and appraised prediction models for 30‐day postoperative mortality in non‐cardiac surgical cohorts. PubMed and Embase were searched up to December 2022 for studies investigating pre‐operative prediction models for 30‐day mortality. We assessed predictive performance in terms of discrimination and calibration. Risk of bias was evaluated using a tool to assess the risk of bias and applicability of prediction model studies. To further inform potential adoption, we also assessed clinical usability for selected models. In all, 15 studies evaluating 10 prediction models were included. Discrimination ranged from a c‐statistic of 0.82 (MySurgeryRisk) to 0.96 (extreme gradient boosting machine learning model). Calibration was reported in only six studies. Model performance was highest for the surgical outcome risk tool (SORT) and its external validations. Clinical usability was highest for the surgical risk pre‐operative assessment system. The SORT and risk quantification index also scored high on clinical usability. We found unclear or high risk of bias in the development of all models. The SORT showed the best combination of predictive performance and clinical usability and has been externally validated in several heterogeneous cohorts. To improve clinical uptake, full integration of reliable models with sufficient face validity within the electronic health record is imperative.